Evaluation of the Feasibility of Transdermal Delivery of Neratinib (NB) Loaded Microneedles to Treat Breast Cancer - Seetharam, Aravindram Attiguppe; Shivananjegowda, Meghana Goravinahalli; Bangarurajan, Krishnarajan; Gowda, Devegowda Vishakante (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Breast cancer is the world’s second-largest leading cause of death in women. Targeting highly localized tumors using transdermal microneedle drug delivery can be highly advantageous in treating breast cancer. Aim The present study evaluates the feasibility of transdermal delivery of promising chemo preventive agent tyrosine kinase inhibitor Neratinib (NB) and physicochemical properties through breast skin and mammary papilla. Materials and Methods The Microneedles (MNs) were fabricated by photo-polymerization method using PEGDA as a biopolymer and TPO as a photo initiator. Optimized (F3) MNs were characterized for stereomicroscopy, Scanning Electron Microscopy (SEM), and mechanical testing. The in vitro permeation studies were carried out on a vertical Franz diffusion cell using porcine skin. Results The cytotoxicity of the optimized formulation on MCF-7 cell lines was carried out using an MTT assay. The FT-IR compatibility studies showed no chemical interaction between drug and excipients used, and an increase in NB solubility decreased the epidermal/vehicle partition coefficient and vice-versa. Microneedles’ pitch and total base diameter were evaluated and found acceptable for the study. The mechanical test confirmed that >30% of the needles penetrated the 3rd and <30% penetrated the 4th layers. The in vitro permeation studies showed that in breast skin and mammary papilla, the highest skin retention of NB was observed with 64% alcohol compared to 32 and 48% alcohol. Microneedles with 32% alcohol significantly increased the permeation of NB, and microneedles increased the cumulative amount of NB permeated through breast skin by 2.9-fold and decreased the lag time by 3.6-fold. However, there was no significant difference in the skin retention amount after pretreatment with microneedles. Conclusion The results showed that the neratinib-loaded microneedles can be used as an effective transdermal delivery for preventing and treating breast cancer.
Keywords: Breast cancer; Microneedles; Tyrosine kinase inhibitors; Transdermal delivery; Neratinib